Navigating with NEMO - Erling Motzfeldt Kravik; Yasin Mimir (Norges Bank, 2019)
This paper describes NEMO, the main dynamic stochastic general equilibrium model used at Norges Bank for monetary policy analysis and forecasting. NEMO has been used to identify the sources of business cycle fluctuations in Norway, to conduct scenario analysis, to produce macroeconomic forecasts, and to conduct monetary policy analysis. The model has recently been re-calibrated and re-estimated to reflect economic conditions since the introduction of inflation targeting in 2001 and other structural changes. This paper presents the estimation of the model using Bayesian methods. It then evaluates its dynamic properties through examining model-based sample moments, conducting impulse response analysis as well as historical shock and forecast-error-variance decompositions, and assessing its forecasting performance against a suite of empirical models. NEMO is used in combination with a broad set of data, empirical models and judgement to make forecasts for key variables in the Norwegian economy. Re-estimation and further development of NEMO are important for the model to continue to be a useful tool for monetary policy analysis.
hdl:11250/2594142
Keywords: 330